Monitoring of Process Flow Diagrams in the Production of Ferrous Metals - Kazhikenova, S. Sh. (Springer US, 2016)
Any improvement in the technological processes involved in the production of ferrous and nonferrous metals, taking into account the existence of lean crude metal and of crude metal that is heterogeneous in terms of composition, should be done not only on the basis of the traditional methods that are used to reveal cause-effect relations in the processes present in the common process flow diagram accompanied by an analysis of their material and heat balances. An additional analysis of these processes is possible on the basis of Shannon information entropy in order to combine as yet uncoordinated indicators on the basis of the content and degree of recovery of valuable components in technological products on the process flow stages and, on the whole, throughout the entire process flow diagram. This is done for the purpose of conducting a comparative analysis and evaluation of the metallurgical processes. Information criteria for an exhaustive evaluation of the uncertainty and degree of completeness of the process flow diagrams of steel production are developed on the basis of an entropy information analysis of the process flow diagrams of ferrous metallurgy.
Keywords: entropy; information; metallurgical process; steel production; entropy information analysis; recovery